The Shifting Role of the Teacher: A Systematic Review of Teacher Perceptions and Practices with AI in the EFL Classroom - Aco, Dedi; Liu, Ming Chou; Sari, Harmita (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This research offers an in-depth examination of the role of Artificial Intelligence (AI) in English as a Foreign Language (EFL) classroom, with a particular emphasis on teachers' perspectives and the integration of technology. It tackles an expanding research gap concerning educators' perceptions and adaptations to AI as it becomes increasingly prevalent in global education. A systematic review of the literature and a bibliometric analysis were performed using the Scopus database on October 13, 2025, resulting in the identification of 180 records. After applying specific inclusion and exclusion criteria, 41 peer-reviewed journal articles were selected for comprehensive analysis. The analysis, facilitated by VOSviewer, highlighted significant research trends, key institutions, and thematic focal points across various educational levels. The findings indicate a significant increase in publications from 2023 to 2025, with Saudi Arabia and Vietnam identified as prominent contributors. Educators predominantly perceive artificial intelligence as a beneficial tool for personalized learning, efficient lesson planning, and formative feedback. However, concerns remain regarding ethical considerations, reliability, and pedagogical readiness. These trends reflect specific aspects of teacher perception, including technological confidence, instructional adaptability, and perceived institutional support. This review is distinguished by its integration of bibliometric mapping with thematic analysis of studies on teacher perceptions, thereby illuminating both the technological and pedagogical aspects of AI integration. The paper concludes by underscoring the implications for professional development and policy, advocating for evidence-based training frameworks that equip EFL educators for responsible and effective AI adoption.